Divided cities Belfast, Beirut, Jerusalem, Mostar, and Nicosia - Calame, Jon (City in the Twenty-First Century, 2011)
Urban planning and conservation experts provide a thorough comparative examination of Belfast, Beirut, Jerusalem, Mostar, and Nicosia--five urban areas physically partitioned in the throes of ethnic conflict.